Effectiveness of quadrivalent influenza vaccination in the first year of a funded childhood program in Queensland, Australia, 2018. Issue 4 (22nd January 2021) - Thangarajah, Dharshi; Malo, Jonathan A.; Field, Emma; Andrews, Ross; Ware, Robert S.; Lambert, Stephen B.
Highlights: From 2018, children aged 6 months to <5 years in Queensland, Australia, were eligible to receive free influenza vaccination. We found the 2018 southern hemisphere childhood injectable quadrivalent influenza vaccine to be moderately effective. Effectiveness increased for children vaccinated according to national guidelines for first season dosage. We demonstrate feasibility of linking local influenza notification data and vaccine register data to monitor vaccine effectiveness. Abstract: Background: Following high influenza activity in 2017, the state of Queensland, Australia, funded a quadrivalent inactivated influenza vaccination program for children aged 6 months to <5 years in 2018. We calculated influenza vaccine effectiveness (VE) among children eligible for this program. Methods: A matched case-control study was conducted. Cases were identified using Queensland 2018 influenza notification data among children age-eligible for funded vaccination. Controls were drawn from Australian Immunisation Register records of Queensland resident children age-eligible for funded influenza vaccine. Up to 10 controls per case were matched for location and birthdate. First dose vaccination was valid if received ≥14 days prior to specimen collection; a second dose was valid if received ≥28 days after first dose receipt. VE was calculated for vaccine doses and adherence to national recommendations for two doses in the first season (schedule completeness) and adjusted (VEadj ) for sex and First Nations status. Results: There were 1, 125 cases and 10, 645 matched controls analysed. Overall VEadj against laboratory-confirmed influenza was 51% (95% confidence interval (CI) 41–60). VEadj was 60% (95% CI 46–70) for children who received two doses in 2018, and 60% (95% CI 48–69) for children vaccinated appropriately according to schedule completeness. VE increased with age. Conclusions: Moderate vaccine effectiveness was observed for children eligible for the funded program in Queensland in 2018, adding to the sparse evidence for influenza vaccine use in Australian children. Adhering to the national first season two dose schedule for influenza vaccine receipt in children ensures maximum protection.